Takotsubo cardiomyopathy in patients suffering from acute non-traumatic subarachnoid hemorrhage—A single center follow-up study - Molnár, Csilla; Gál, Judit; Szántó, Dorottya; Fülöp, László; Szegedi, Andrea; Siró, Péter; Nagy, Endre V.; Lengyel, Szabolcs; Kappelmayer, János; Fülesdi, Béla (PloS one, 2022)
Takotsubo cardiomyopathy (TTC) is an important complication of subarachnoid hemorrhage (SAH), that may delay surgical or endovascular treatment and may influence patient outcome. This prospective follow-up study intended to collect data on the prevalence, severity, influencing factors and long-term outcome of TTC in patients suffering from non-traumatic SAH. Consecutive patients admitted with the diagnosis of non-traumatic SAH were included. Intitial assessment consisted of cranial CT, Hunt-Hess, Fisher and WFNS scoring, 12-lead ECG, transthoracic echocardiography (TTE), transcranial duplex sonography and collecting laboratory parameters (CK, CK-MB, cardiac troponin T, NT-proBNP and urine metanephrine and normetanephrine). Diagnosis of TTC was based on modified Mayo criteria. TTC patients were dichotomized to mild and severe forms. Follow-up of TTE, Glasgow Outcome Scale assessment, Barthel's and Karnofsky scoring occurred on days 30 and 180. One hundred thirty six patients were included. The incidence of TTC in the entire cohort was 28.7%; of them, 20.6% and 8.1% were mild and severe, respectively. TTC was more frequent in females (30/39; 77%) than in males (9/39; 23%) and was more severe. The occurrence of TTC was related to mFisher scores and WFNS scores. Although the severity of TTC was related to mFisher score, Hunt-Hess score, WFNS score and GCS, multivariate analysis showed the strongest relationship with mFisher scores. Ejection fraction differences between groups were present on day 30, but disappeared by day 180, whereas wall motion score index was still higher in the severe TTC group at day 180. By the end of the follow-up period (180 days), 70 (74.5%) patients survived in the non-TTC, 22 (81.5%) in the mild TTC and 3 (27%) in the severe TTC group (n = 11) (p = 0.002). At day 180, GOS, Barthel, and Karnofsky outcome scores were higher in patients in the control (non-TTC) and the mild TTC groups than in the severe TTC group. Takotsubo cardiomyopathy is a frequent finding in patients with SAH, and severe TTC may be present in 8% of SAH cases. The severity of TTC may be an independent predictor of mortality and outcome at 6 months after disease onset. Therefore, a regular follow-up of ECG and TTE abnormalities is warranted in patients with subrachnoid hemorrhage for early detection of TTC. The study was registered at the Clinical Trials Register under the registration number of NCT02659878 (date of registration: January 21, 2016).